Studı Kualıtatıf Mengenaı Faktor Penerımaan Aplıkası E-Commerce Shopee Dan Fıntech Shopeepay Bagı Masyarakat Senıor - Leonardo Anthony; Hendi Sama (Universitas Internasional Batam, 2021)
Shopee e-commerce is used to do shopping activities anywhere and anytime and has Shopeepay payment fintech. The shopee application produces a shopping system that suits the needs of its users for adolescents and adults. It is possible for the senior community to also use it. Here the researcher wants to find out whether Shopee and Fintech Shopeepay can be accepted by the senior community as a tool for searching and shopping online. This research is a qualitative research, using the TAM (Technology Acceptance Model) approach with the interview method. The results of this study concluded that Shopee was not fully accepted by the senior community